2005
DOI: 10.1074/jbc.m400893200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-scanning Mutagenesis of Muscle Carnitine Palmitoyltransferase I Reveals a Single Cysteine Residue (Cys-305) Is Important for Catalysis

Abstract: Carnitine palmitoyltransferase (CPT) I catalyzes the conversion of long-chain fatty acyl-CoAs to acyl carnitines in the presence of L-carnitine, a rate-limiting step in the transport of long-chain fatty acids from the cytoplasm to the mitochondrial matrix. To determine the role of the 15 cysteine residues in the heart/skeletal muscle isoform of CPTI (M-CPTI) on catalytic activity and malonyl-CoA sensitivity, we constructed a 6-residue N-terminal, a 9-residue C-terminal, and a 15-residue cysteineless M-CPTI by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This observation invited speculation that the thiol group in cysteines might be required in the formation of an acyl-S-enzyme before desaturation took place and be important for the overall stabilization of the protein (28). Moreover, cysteine-scanning mutagenesis study on muscle carnitine palmitoyltransferase I, which also utilizes acyl-CoAs as substrates, has revealed that a single cysteine is important for catalysis, probably serving as the site for the covalent attachment of the acylCoAs (51). In addition to that, Reiser and Raju (49) have also provided evidence that the inhibition of the desaturase by cyclopropene fatty acyl-CoAs is due to the irreversible binding of the sulfhydryl groups of the enzyme by the cyclopropene group.…”
Section: Discussionmentioning
confidence: 99%
“…This observation invited speculation that the thiol group in cysteines might be required in the formation of an acyl-S-enzyme before desaturation took place and be important for the overall stabilization of the protein (28). Moreover, cysteine-scanning mutagenesis study on muscle carnitine palmitoyltransferase I, which also utilizes acyl-CoAs as substrates, has revealed that a single cysteine is important for catalysis, probably serving as the site for the covalent attachment of the acylCoAs (51). In addition to that, Reiser and Raju (49) have also provided evidence that the inhibition of the desaturase by cyclopropene fatty acyl-CoAs is due to the irreversible binding of the sulfhydryl groups of the enzyme by the cyclopropene group.…”
Section: Discussionmentioning
confidence: 99%
“…Asp213 and Glu487 are affected by naturally occurring mutations and have been determined to be important for CPT-2 function by biochemical analyses (Zheng et al, 2002;Liu et al, 2005). Asp213 is located in a loop between b3 and a10 of CPT-2 and aligns with a cysteine conserved in all human CPT-1 isoforms.…”
Section: Cpt-2 Deficiencymentioning
confidence: 99%
“…When a mutant C304W of L-CPTI observed with one of their patients was expressed in COS cells, it was not effectively expressed and showed no catalytic activity. In the other approach, Woldegiorgis and his colleagues carried out Cys-scanning mutagenesis to determine the roles of 15 Cys residues present in M-CPTI (Liu et al 2005). Using C305W 8 a CPTI activity observed with mitochondrial fraction prepared from each transfectants, as % of that observed with transfectant of wild type.…”
Section: Resultsmentioning
confidence: 99%
“…The only exceptionally acceptable amino acid as a substitute for C305 of M-CPTI was Asp. Liu et al (2005) carried out alignments of the amino acid sequence of CPTI with the acyltransferase family of enzymes and, based on the results of past mutation studies, identified conserved catalytically important residues C305, D454, and H473 for the acyltransferase activity of CPTI. Of these, D454 and H473 are conserved not only in CPTI and CPTII but also in the other acyltransferases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation